2018
DOI: 10.1016/j.jtho.2018.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death 1 Blockade With Nivolumab in Patients With Recurrent Malignant Pleural Mesothelioma

Abstract: Single-agent nivolumab has meaningful clinical efficacy and a manageable safety profile in pre-treated patients with mesothelioma. PD-L1 expression does not predict for response in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
152
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 213 publications
(169 citation statements)
references
References 32 publications
5
152
4
1
Order By: Relevance
“…A singlecenter, single-arm phase II study, the NivoMes trial, with single-agent nivolumab, an anti-PD-1 antibody showed that 16 (47%) of the 34 registered patients with recurrent MPM achieved disease control at 12 weeks (8 with Open access partial response (PR) and 8 with stable disease (SD)). 53 In this population, PD-L1 expression did not predict treatment responses. A Japanese single-arm phase II study, the MERIT study, also examined the efficacy and safety of nivolumab monotherapy in 34 patients with MPM with a history of prior chemotherapy.…”
Section: Single-agent Ici Therapy In the Salvage Settingmentioning
confidence: 78%
See 1 more Smart Citation
“…A singlecenter, single-arm phase II study, the NivoMes trial, with single-agent nivolumab, an anti-PD-1 antibody showed that 16 (47%) of the 34 registered patients with recurrent MPM achieved disease control at 12 weeks (8 with Open access partial response (PR) and 8 with stable disease (SD)). 53 In this population, PD-L1 expression did not predict treatment responses. A Japanese single-arm phase II study, the MERIT study, also examined the efficacy and safety of nivolumab monotherapy in 34 patients with MPM with a history of prior chemotherapy.…”
Section: Single-agent Ici Therapy In the Salvage Settingmentioning
confidence: 78%
“…54 Overall, anti-PD-1 antibodies exhibited promising results when used alone as a salvage therapy after the firstline chemotherapy. [53][54][55][56] unresolved, unmet needs for MPM ICI therapy Compared with clinical trials targeting other malignancies, the majority of prior MPM trials employed 'small-scale' and 'single-arm' designs, and their primary endpoints were set at only ORR or DCR. No clear survival advantage of ICI has been demonstrated through randomized trials.…”
Section: Ici Combination Therapy In Salvage Settingsmentioning
confidence: 99%
“…6 Similar results were obtained in single-arm phase II studies with pembrolizumab or nivolumab with or without ipilimumab ( Table 1). [7][8][9][10] Currently, the additional value of ipilimumab to nivolumab in MPM is still not clear. Scherpereel et al 9 initiated a randomized phase II study of nivolumab ± ipilimumab.…”
mentioning
confidence: 99%
“…In this context, the publication this month of two promising phase II studies in previously-treated MPM represents important progress. [refs Scherpereel et al, 2018, Disselhorst et al, 2018 Both trials investigated immune checkpoint inhibitors (ICI), used singly or in combination. These agents, which enable perseveration of anti-tumour immune activity by preventing down-regulation of antigenspecific T cells, have yielded impressive results in other poor-prognosis malignancies and recently earned the scientists behind their discovery the Nobel Prize in Medicine.…”
mentioning
confidence: 99%
“…4 The results reinforce other early-phase studies of ICI in MPM, including the non-randomised NivoMes trial, which demonstrated DCR of 47% and 1-year survival rates of 50% in MPM patients treated with single-agent nivolumab. 5 Combination nivolumab and ipilimumab has not been studied in MPM before, but an alternative PD1/CTLA4 combination, durvalumab and tremelimumab, was used in the NIBIT-meso-1 trial. 40 patients were treated, in the first or second-line setting, of whom 23 (63%) demonstrated disease control, with a PFS of 5·7 months and MOS of 16·6 months.…”
mentioning
confidence: 99%